Assessment of impact of a skin cancer education session on cosmetology students' knowledge and preparedness to assess future clients for skin lesions. (13th May 2019) - Radisic, Anna; Hundley, Kelsey; Patel, Nishit; Nelson, Christopher; Mhaskar, Rahul
Abstract: Background: Approximately 50% of cutaneous melanomas go undetected by patient self‐inspection, and lesions that go unnoticed are usually located on the scalp, head, and neck. Cosmetologists are able to examine areas difficult to see on self‐inspection. Objectives: The purpose of this study was to design and conduct an educational skin cancer screening presentation for cosmetology students and assess preparedness to discuss skin cancer with future clients. Methods: This cross‐sectional study conducted and analyzed in 2017 assessed the efficacy of a skin cancer education presentation among cosmetology students. Students completed a pre‐/poststyle quiz aimed at assessing skin cancer knowledge. The difference in pre‐ and postknowledge quiz was analyzed using paired samples t test. Results: A total of 194 students from seven cosmetology schools participated. Before the presentation, 43.4% felt underprepared to check for unusual lesions on future clients while 17.7% felt some level of preparedness. After, 3% felt underprepared while 51% felt prepared. There was a statistically significant difference in the skin cancer knowledge quiz total score before (M = 7.87, SD = 1.493) and after (M = 9.23, SD = 1.037) the educational presentation ( P  < 0.0001). Conclusions: This study shows most cosmetology students in the Tampa Bay area appear to be interested in learning more about skin cancer and agree that curricula should include skin cancer topics. Results of this study were limited to the Tampa Bay area and may not represent national trends. However, skin cancer presentation and screening‐related content could be included in cosmetology curricula to help better prepare cosmetologists to screen for suspicious skin lesions.